New fractional inequalities of Ostrowski-Grüss type - Mehmet Zeki Sarikaya (Le Matematiche, 2014)
In this paper, we improve and further generalize some Ostrowski-Grüss type inequalities for the fractional integrals by using new Montogomery identities.